The consciousness of virtue: uncovering the gaps between educational specialists and the general public in their understanding of virtue in Japan - Tachibana, Koji; Nakazawa, Eisuke (Frontiers in Psychology, 2024)
Virtue is a normative concept that constitutes social and moral codes. The notion of virtue can be identified in both the West and the East. Since this concept was revived in academia in the 20th century after a long sinking into oblivion, contemporary professional researchers, but not the general public, may be familiar with this notion. We conducted a survey on the attitudes of experts and the general public regarding the notion of virtue in Japan. Our study found that, in contrast to experts, the general public were not so familiar with the notion; both had a positive image of virtue and a poor understanding of the Confucius notions of virtue; both retain Buddhist values under the term of virtue, but experts tended to associate ancient Greek and Western elements with virtue. Experts emphasized active, intellectual virtues as practical wisdom, whereas the general public emphasized passive, emotional virtues, such as gratitude. Hence, the notion of virtue is understood in different ways between experts and the general public in Japan. This finding has several social implications, such as academic integrity and educational policy.